The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.3354/meps08877
|View full text |Cite
|
Sign up to set email alerts
|

Baiting sharks for marine tourism: Comment on Clua et al. (2010)

Abstract: A recent study by Clua et al. (2010; Mar Ecol Prog Ser 414:257-266) that looks at the behavioural response of sicklefin lemon sharks Negaprion acutidens to underwater feeding for ecotourism purposes has a number of methodological and semantic problems that complicate the evaluation of the results and raise questions about the conclusions. Main issues are the lack of a control, the use of non-defined terms to characterize observed behaviours, and statements not supported by data. Unwarranted conclusions include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Provisioning food is a means of attracting wildlife to facilitate human interaction, and though it is a widespread practice, its long-term ecological implications need further investigation ( Orams, 2002 ; Dobson, 2006 ). Reliable shark encounters are difficult, promoting the use of provisioning activities to attract them ( Gallagher & Hammerschlag, 2011 ; Hammerschlag et al, 2012 ) These are controversial as sharks are apex predators, and some provisioned species are potentially dangerous to humans and may impact their ecological function ( Brunnschweiler & McKenzie, 2010 ). In the Red Sea, tagged silky sharks, Carcharhinus falciformis , had modified local habitat use and increased presence on days when baiting occurred ( Clarke, Lea & Ormond, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Provisioning food is a means of attracting wildlife to facilitate human interaction, and though it is a widespread practice, its long-term ecological implications need further investigation ( Orams, 2002 ; Dobson, 2006 ). Reliable shark encounters are difficult, promoting the use of provisioning activities to attract them ( Gallagher & Hammerschlag, 2011 ; Hammerschlag et al, 2012 ) These are controversial as sharks are apex predators, and some provisioned species are potentially dangerous to humans and may impact their ecological function ( Brunnschweiler & McKenzie, 2010 ). In the Red Sea, tagged silky sharks, Carcharhinus falciformis , had modified local habitat use and increased presence on days when baiting occurred ( Clarke, Lea & Ormond, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent work has demonstrated that observational techniques may be prone to some bias (Meyer et al. 2009a,b; Brunnschweiler & Baensch 2010; Brunnschweiler & McKenzie 2010) and reinforce the need for remote monitoring tools, particularly acoustic and satellite telemetry, to evaluate the ecological impacts of ecotourism on shark behaviour (Sims 2010; Hammerschlag, Gallagher & Lazarre 2011). To our knowledge, only four published studies have used telemetry to address these issues, with conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…However, at present, the debate has been largely rhetorical because of lack of sufficient quantitative data to either support or refute various hypotheses regarding apex predator conditioning and behaviourally or ecologically mediated effects (Meyer et al. 2009b; Brunnschweiler & McKenzie 2010).…”
Section: Introductionmentioning
confidence: 99%